ANALISIS DAMPAK LINGKUNGAN DARI KINERJA RUAS JALAN IMAM BONJOL KABUPATEN ACEH BARAT TERHADAP TINGKAT KEBISINGAN - Yusra, Cut Liliiza; Erliana, Hilma (Lingkar: Journal of Environmental Engineering, 2023)
The improvement of urban road infrastructure is a crucial aspect of development, yet it is often accompanied by environmental impacts that need careful consideration. One of the environmental issues that arises is noise pollution, especially in urban areas experiencing high growth in the transportation sector. The research aims to evaluate the relationship between road service levels and noise levels. The analysis of the data reveals that the highest peak hour volume occurs on Mondays from 12:00 to 12:15, with a value of 133.8 vehicles per hour (vph), followed by Sundays from 16:00 to 16:15 with 130.7 vph. The road capacity reaches 1484.05 vph with a Volume-to-Capacity Ratio (DS) of 0.101 (DS < 0.75), indicating good service levels. The free-flow speed of vehicles on Imam Bonjol street is 34.06 km/h. Overall, the road is categorized at service level B. However, the noise level generated by vehicles around this road is quite high, exceeding the established quality standards ranging from 58 to 63 dB. The highest values occur on weekdays, especially during peak hours, indicating that traffic volume and surrounding activities influence noise levels. Noise exceeding the standard limits can have negative impacts on human health and environmental comfort.